Penerapan Algoritma Linear Regression Dalam Memprediksi Harga Saham Bank BRI - Andi Diah Kuswanto; Auliya Putri Amanda; Yoseba Priscilla; Maranatha Magdalena; Ananti Putri Safira; Izza Maulida (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2023)
Investment is the act of placing funds in the hope of getting additional money or profits. Basically, investing involves placing a certain amount of funds today in the hope of making a profit in the future. From this understanding, it can be concluded that stock investment is the allocation of current sources of funds with the hope of gaining profits in the future through purchasing securities in the form of shares. The aim is to obtain additional or certain profits from the funds invested in trading shares on the stock exchange.